IMPLEMENTASI ALGORITMA FP-GROWTH UNTUK MENUNJANG KEPUTUSAN PERSEDIAN BARANG DI CV INDOTECH JAYA SENTOSA KOTA CIREBON - Iman Nurrohmat; Odi Nurdiawan; Agus Bahtiar (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
Indotech Jaya Sentosa is a company engaged in trading in the form of computers and network infrastructure. Currently experiencing problems in managing inventory for its customers. These obstacles include the frequent occurrence of overcapacity in storage warehouses that exceeds the number of requests, even more so in the era of the Covid-19 pandemic. This study aims to provide a solution to the problems at CV Jaya Sentosa, namely by applying a technique or algorithm to support decisions in managing its merchandise inventory. The approach taken is to use a data mining approach involving the FP-Growth algorithm method. FP-Growth Algorithm is a method to find the pattern of relationship between one or more items in a dataset. While the steps taken to the data mining approach include business understanding, data understanding, data preparation, data modeling, data evaluation and deployment. The final result of this research is expected to be able to apply association rules where these rules can be used as a reference in predicting what kind of inventory should be held to facilitate inventory management.